2017
DOI: 10.1097/ico.0000000000001481
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Transplantation in New Zealand 2000 to 2009

Abstract: In this study of 941 consecutive, principally penetrating, corneal transplants, adverse events were found to be more common than typically reported. In an era in which PKP is increasingly substituted by lamellar surgery, this provides useful insight into operative and postoperative adverse events in penetrating surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
1
10
0
2
Order By: Relevance
“…Ethnicity, rejection and graft failure appear to be interlinked in the results from this study and it is difficult to separate the three. Corneal allograft rejection was the leading cause of PK graft failure in a previous Auckland study, and ethnicity was found to be a significant risk factor for graft rejection on multivariate analysis . A further study from the same group found that Maori and Pacific Island ethnicities were observed to have the lowest level of follow‐up attendance following corneal transplant .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Ethnicity, rejection and graft failure appear to be interlinked in the results from this study and it is difficult to separate the three. Corneal allograft rejection was the leading cause of PK graft failure in a previous Auckland study, and ethnicity was found to be a significant risk factor for graft rejection on multivariate analysis . A further study from the same group found that Maori and Pacific Island ethnicities were observed to have the lowest level of follow‐up attendance following corneal transplant .…”
Section: Discussionmentioning
confidence: 87%
“…Corneal allograft rejection was the leading cause of PK graft failure in a previous Auckland study, and ethnicity was found to be a significant risk factor for graft rejection on multivariate analysis. 16 A further study from the same group found that Maori and Pacific Island ethnicities were observed to have the lowest level of follow-up attendance following corneal transplant. 29 The authors did not find a statistically significant correlation between appointment attendance and subsequent graft failure; however, they acknowledged that the lower attendance rate may cause under-detection of graft failure.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nonetheless, the most common cause of corneal allograft failure remains cell‐mediated rejection . In addition to allograft rejection, penetrating keratoplasty is also associated with significant ametropia, astigmatism and common complications related to corneal sutures …”
mentioning
confidence: 99%